CAROTID BODY FUNCTION IN HEART FAILURE - Schultz, Harold D. (2007)
In this review, we summarize the present state of knowledge of the functional characteristics of the carotid body (CB) chemoreflex with respect to control of sympathetic nerve activity (SNA) in chronic heart failure (CHF). Evidence from both CHF patients and animal models of CHF has clearly established that the CB chemoreflex is enhanced in CHF and contributes to the tonic elevation in SNA. This adaptive change derives from altered function at the level of both the afferent and central nervous system (CNS) pathways of the reflex arc. At the level of the CB, an elevation in basal afferent discharge occurs under normoxic conditions in CHF rabbits, and the discharge responsiveness to hypoxia is enhanced. Outward voltage-gated K(+) currents (I(K)) are suppressed in CB glomus cells from CHF rabbits, and their sensitivity to hypoxic inhibition is enhanced. These changes in I(K) derive partly from downregulation of nitric oxide synthase (NOS) / NO signaling and upregulation of angiotensin II (Ang II) / Ang II receptor (AT(1)R) signaling in glomus cells. At the level of the CNS, interactions of the enhanced input from CB chemoreceptors with altered input from baroreceptor and cardiac afferent pathways and from central Ang II further enhance sympathetic drive. In addition, impaired function of NO in the paraventricular nucleus of the hypothalamus participates in the increased SNA response to CB chemoreceptor activation. These results underscore the principle that multiple mechanisms involving Ang II and NO at the level of both the CB and CNS represent complementary and perhaps redundant adaptive mechanisms to enhance CB chemoreflex function in CHF.